Accident rate among children - Lachowski, Stanisław (Polish Journal of Public Health, 2009)
Injuries due to accidents are the greatest health problem among children and adolescents. From the beginning of the 90s a systematic decrease has been observed in the number of deaths caused by accidents among children; however, this rate is considerably higher compared to that noted in West European countries. Accidents are the cause of approximately 70% of deaths among children and adolescents. Simultaneously, the percentage of accidents resulting in injuries requiring hospitalization remains high. In recent years, the number of these events has been increasing. In 2008, approximately 70,000 children aged 5-14 required hospital treatment due to accident injuries. Compared to 2003, the value of accident-related morbidity increased by 25%. An especially unfavourable situation was noted in the rural environment, where the accident rate increased by 33.3% - and among rural girls – by 42%. One of the causes of high accident rates among rural children is their engagement in work activities on family farms. Data by the Agricultural Social Insurance Fund (KRUS) indicates that every year about 1,400 children aged 15 are victims of accidents while performing agricultural work activities. It seems justifi able to monitor the accident rates among children.